Endoplasmic reticulum stress remodels alveolar bone formation after tooth extraction - Chen, Yun; Guo, Yue; Li, Jun; Chen, Ying‐Yi; Liu, Qiong; Tan, Li; Gao, Zheng‐Rong; Zhang, Shao‐Hui; Zhou, Ying‐Hui; Feng, Yun‐Zhi (Journal of cellular and molecular medicine, 2020)
Bone healing in tooth extraction sockets occurs in a complex environment containing saliva and many microorganisms and is affected by many factors. Endoplasmic reticulum (ER) stress affects bone metabolism, but the role of ER stress in bone healing after tooth extraction remains unclear. We utilized a rat tooth extraction model, in which we promoted wound healing by using salubrinal to regulate the ER stress response. Western blot analysis showed increased expression of p‐eIF2α/eIF2α, Runx2 and alkaline phosphatase (ALP) in bone tissue, and histological assays showed irregularly arranged and new bone with more collagen fibres 14 days after tooth extraction and after modulating the degree of ER stress. Micro‐CT showed that modulating ER stress to an appropriate degree increases bone filling in regards to the density in the bottom and the surrounding bone wall of the tooth extraction wounds. Transmission electron microscopy showed rough ER expansion and newly formed collagen fibrils in osteoblasts after modulating ER stress to an appropriate degree. We also used different concentrations of salubrinal to evaluate the resistance to tunicamycin‐induced ER stress in an osteogenic induction environment. Salubrinal restored the tunicamycin‐induced decrease in the viability of primary calvarial osteoblasts and increased the expression of Runx2 and ALP, and decreased p‐eIF2α/eIF2α in a dose‐dependent manner. Taken together, the results demonstrate that ER stress occurred after tooth extraction, and regulating the degree of ER stress can promote bone healing in tooth extraction sockets, providing clinical evidence for bone healing.